2004
DOI: 10.1186/1471-2121-5-39
|View full text |Cite
|
Sign up to set email alerts
|

Production of hemo- and immunoregulatory cytokines by erythroblast antigen+ and glycophorin A+ cells from human bone marrow

Abstract: Background: Erythroid nuclear cells (ENC) of the bone marrow (BM) have not previously been considered as important producers of wide spectrum of haemo-and immunoregulatory cytokines. The aim of the current work was to confirm the production of the main hemo-and immunoregulatory cytokines in human ENC from BM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…We confirmed production of IL-1β, IL-2, IL-4, IL-6, IL-10, IFN-γ, and TNF-α by human bone marrow glycophorin A-positive cells [8] and revealed production of IL-8, IL-13, IL-17, G-CSF, GM-CSF, MCP-1, and MIP-1β by these cells (Table 1). IL-5, IL-7, and IL-12 were not detected and we concluded that bone marrow NEC cannot secrete these proteins under specified culturing conditions.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…We confirmed production of IL-1β, IL-2, IL-4, IL-6, IL-10, IFN-γ, and TNF-α by human bone marrow glycophorin A-positive cells [8] and revealed production of IL-8, IL-13, IL-17, G-CSF, GM-CSF, MCP-1, and MIP-1β by these cells (Table 1). IL-5, IL-7, and IL-12 were not detected and we concluded that bone marrow NEC cannot secrete these proteins under specified culturing conditions.…”
Section: Resultssupporting
confidence: 87%
“…Previous studies showed that human bone marrow NEC produce IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-13, IL-17, IFN-γ, TNF-α, G-CSF, GM-CSF, MCP-1, TGF-β 1 , MIP-1β, erythropoietin, and vascular endothelial growth factor under normal conditions [4,8,11]. Therefore, these cells possess high immunoregulatory potentcy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility to disease is determined by a combination of allelic variants of genes in the individual genotype forming unfavorable hereditary background, which is realized during the interaction with Mycobacterium tuberculosis. Recent advances in molecular genetics open new perspectives in studying the pathogenesis of tuberculosis: genes whose expression products are involved in the infectious process were identifi ed [1,6].…”
mentioning
confidence: 99%
“…Functional activity of the cytokine network during tuberculosis depends on a variety of factors, including individual differences in the production of immunoregulatory molecules determined by some genetic peculiarities [3,6,10,12]. The search for predictors of susceptibility to infection among cytokine gene alleles is a new perspective trend of research [5].…”
mentioning
confidence: 99%